Simply Bead & Wire : 20 Jewelry Projects - Crafts, Lark; Published by Lark Craft (New York Lark Crafts, 2011)
Based on the book "Contemporary Bead & Wire Jewelry", this title collects together 20 projects. It teaches the basic techniques and provides a collection of projects for budding jewelers, from gold filigree earrings with carnelian beads to a pearl-accented pendant of gleaming amber, each piece is stunning.
Include Color Illustration
Keywords: Wire craft -- Beadwork -- Jewelry making